What Can Theology Offer Psychology? Some Considerations in the Context of Depression - Jessica Coblentz (Journal of Moral Theology, 2020)
This paper explores what recent theological debates about human suffering might afford psychology as it continues to engage realities of suffering, especially persistent depression. It argues that these debates invite psychology to consider the limits and the morality of the scientific framework that it brings to human suffering. In light of this, psychology might benefit from how theology has revised its approaches to suffering in recent decades. The paper proceeds in three parts. First, it introduces “theodicy,” the modern theological approach to suffering that has been at the center of these debates, and then demonstrates that theodicy and psychology bring to human suffering a number of similar theoretical presuppositions. Second, the paper introduces recent theological critiques of theodicy and identifies evidence of psychology’s own complicity in theodicy’s theoretical failings. Part three explores how theologians have attempted to move beyond theodicy and argues that theology’s alternative strategies for representing and responding to suffering might interest psychology and serve as an avenue for collaboration between the disciplines.